Cytogenetics for the study of telomere function in plants - Siroky, J (Cytogenetic and genome research, 2008)
The ends of linear chromosomes of the vast majority of eukaryotic species possess specialized nucleo-protein structures called telomeres. Regardless of many exceptions, the structure and function of telomeres share high degrees of similarity between various eukaryotes. The underlying DNA structure of telomeres determines the particular setup of telomere chromatin and protein complexes as are telomere-associated proteins and a number of repair and cell cycle checkpoint agents. The structure of telomeres is highly dynamic during the cell's growth, replication, differentiation, senescence, or neoplastic transformation. Although the bulk of our knowledge about telomere function comes from molecular and biochemical studies in model organisms such as yeast and mouse, we want to show--with special emphasis on plants--in this short review that classical methods of plant cytogenetics can significantly complement the above experimental approaches and help in our understanding of telomere functions.
Keywords: Plants; proteiny huseníčku; DNA, Plant; telomerasa; Chromosomes, Plant; telomery; fyziologie rostlin; cytogenetické vyšetření; oprava DNA; Telomerase; Arabidopsis Proteins; DNA Repair; Arabidopsis; Telomere; Plant Physiological Phenomena; Plant Cells; DNA rostlinná; chromozomy rostlin; Cytogenetic Analysis; rostliny; rostlinné buňky